Viability Planning, Value Capture and the Geographies of Market-Led Planning Reform in England. (14th March 2020) - Ferm, Jessica; Raco, Mike
ABSTRACT: This paper focuses on the contentious transition to viability-driven planning in England, whereby development viability and the potential for land value capture dominate the work of planning. Drawing on interviews and fieldwork in London and the north east of England, the paper reflects on the variable outcomes and challenges in places with different development markets, political cultures, development histories and capacities for action. It finds that viability-driven planning is further entrenching already existing spatial disparities and inequalities and draws conclusions about the state of English urban policy in the context of a broader shift towards the marketisation of planning.